Gimnazjaliści w epoce wtórnej oralności. Analiza wybranych wypowiedzi pisemnych - Rypel, Agnieszka (Polonistyka. Innowacje, 2015)
The issue of the article concerns the literacy of the young generation of Poles. The author shows how the texts written by secondary school students are changing under the influence of new media, the expansion of visual perception of the world and the universal acceptance of informality in the way of thinking and language use. A particular attention is given to a situational text index and interactivity. The exemplary material comes from a variety of works written by junior high school students who took part in a nationwide research.